433 Independent impact of metabolic syndrome on left ventricular longitudinal dysfunction in type 2 diabetes mellitus. (17th January 2020) - Casciano, O; Luciano, F; Cocozza, S; Sorrentino, R; Lembo, M; Sellitto, V; Santoro, C; Esposito, R; Rivellese, A; Galderisi, M
Abstract: Background: The risk of cardiovascular (CV) disease in type 2 diabetes mellitus (T2DM) is highly heterogeneous and an adequate risk stratification is needed. CV risk mainly depends on concomitant risk factors, combined in the metabolic syndrome (MetS). Echocardiography is an useful tool for diagnosis of cardiac organ damage and CV risk stratification in T2DM. Purpose: To investigate the effects of MetS on left ventricular (LV) structure and function in patients with T2DM with normal LV ejection fraction (LVEF) and without overt coronary artery disease (CAD) and heart failure symptoms/signs. Methods: We prospectively recruited 384 consecutive, uncomplicated T2DM patients. All patients underwent clinical exam, blood sampling and complete echo-Doppler exam, including determination of 2D-echo derived global longitudinal strain (GLS). LV mass index ≥45 g/m^2.7 in women and ≥49 g/m^2.7 in men was used to characterize LV hypertrophy. LV longitudinal dysfunction was assumed for GLS < 20% in absolute values. LV diastolic dysfunction was identified according to 2016 ASE/EACVI recommendations. MetS was defined according to NCEP-ATP III criteria. Significant CAD including previous myocardial infarction, LV systolic dysfunction (= LVEF <50%), hemodinamically significant valvular heart disease, primary cardiomyopathies, permanent atrial fibrillation, glomerular filtration rate <30 ml/min and inadequate echo images were exclusion criteria. The study population was divided according to presence of MetS. Results: 66% of the patients (254/384) met the criteria for MetS diagnosis. They had comparable age and heart rate with controls. Diabetic patients with MetS had higher glycated haemoglobin (HbA1c) (7.2 ± 1.3 vs. 6.9 ± 1.0%, p = 0.023) and uric acid (5.5 ± 1.4 vs. 4.9 ± 1.3 mg/dl, p = 0.001) than those without, and lower glomerular filtration rate (69.5 ± 15.0 vs 74.0 ± 12, 1 ml/min, p = 0.004). MetS patients showed a higher LV mass index (p < 0.0001) and a greater prevalence of both LV hypertrophy (31.9 vs 12.5%, p < 0.0001) and diastolic dysfunction (52.6 vs. 32.8%, p = 0.007) (Figure). T2DM patients with MetS also had lower GLS (20.6 ± 2.1 vs. 21.9 ± 2.2%, p = 0.001), with a greater prevalence of LV longitudinal dysfunction (38.2 vs. 24.7%, p = 0.049) (Figure). After adjusting for age, T2DM duration, sex, HbA1c, uric acid, LV mass index and LV diastolic dysfunction by a multiple regression analysis in the pooled population, GLS reduction was independently associated with MetS (β coefficient = -0.184, p < 0.02) and LV mass index (β= -0.94, p = 0.04). Conclusion: In patients with T2DM, the presence of MetS induces a greater prevalence not only of LV hypertrophy and diastolic dysfunction but also of LV longitudinal deformation impairment. GLS reduction in diabetic patients is associated with MetS independently of confounders including glycemic control and diabetic duration.